Preparation process of wear-resistant high-entropy alloy

Ni20Cr15Mo10Co5W5Nb3Ti2B2Si high-entropy alloy was prepared through powder metallurgy and vacuum arc furnace smelting processes, solving the problems of high-entropy alloy high-entropy alloy high-processing cost and tribological research lag, and achieving high-efficiency and low-cost wear resistance and oxidation resistance improvement.

CN119194202APending Publication Date: 2024-12-27SHAANXI AEROSPACE INTELLIGENT MANUFACTURING NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411317436.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

There are high cost and difficulty in processing high entropy alloys. Traditional smelting methods cost more to manufacture parts, and the tribological research of high entropy alloys is slow to develop under conventional working conditions, and lacks efficient replacement of wear-resistant materials. plan.

Method used

The high-entropy alloy is prepared by powder metallurgy method. Through the vacuum arc furnace smelting process, the element ratio and process parameters are adjusted to form Ni20Cr15Mo10Co5W5Nb3Ti2B2Si alloy with excellent wear resistance and high temperature performance, and the combination of elements such as Cr, Mo, Ni, Ti is improved. The strength, wear resistance and oxidation resistance of the alloy.

Benefits of technology

It realizes efficient preparation of wear-resistant high-entropy alloys, reduces manufacturing costs, improves the structural uniformity and composition uniformity of parts, significantly improves the high-temperature wear resistance and oxidation resistance of the alloy, and reduces the friction coefficient and wear rate.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation process of a wear-resistant high-entropy alloy, and relates to the technical field of high-entropy alloys, the wear-resistant high-entropy alloy comprises the following elements: 15%-25% of Ni, 10%-20% of Cr, 5%-15% of Mo, 1%-10% of Co, 1%-10% of W, 2%-4% of Nb, 1%-3% of Ti, 1%-3% of B and 0.5%-1.5% of S. According to the high-entropy alloy, Cr is added into Ni20Cr15Mo10Co5W5Nb3Ti2B2Si, so that the strength and wear resistance of the alloy are improved by forming an o phase with Mo, meanwhile, the oxide Cr2O3 is beneficial to improving the oxidation resistance and has a good high-temperature lubricating effect in the high-temperature friction process, and Ni serves as a good FCC phase stabilizer and is beneficial to enabling the high-entropy alloy to have high plasticity and toughness; ti is used for improving the high-temperature wear resistance of the high-entropy alloy by forming TiO2 in the high-temperature friction process, and Mo is used for triggering lattice distortion and enhancing the strength, hardness and wear resistance of the high-entropy alloy by means of the large atomic radius of Mo; and meanwhile, Mo and Cr form an O phase, so that the high-temperature mechanical property of the alloy is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high entropy alloys, and in particular to a preparation process of a wear-resistant high entropy alloy. Background Art

[0002] Titanium alloys have good comprehensive properties, such as low material density, high specific strength, high fracture toughness, high fatigue strength, and excellent corrosion resistance, and are increasingly widely used in biomedicine, high temperature conditions, marine engineering, and aerospace.

[0003] At present, high entropy alloys are mostly made by smelting, and the manufacturing of parts requires further mechanical processing. The high performance of high entropy alloys makes processing difficult. Therefore, the cost of manufacturing high entropy alloy parts by traditional methods is relatively high. The use of powder metallurgy has the advantages of saving materials, high efficiency, and the manufactured parts have uniform organization and composition.

[0004] The tribological research of high entropy alloys under normal working conditions has developed relatively rapidly. Its excellent wear resistance and cost advantages make it an ideal choice to replace traditional wear-resistant materials and improve the reliability and service life of related machinery or tools. High entropy alloys have high entropy effects in thermodynamics, lattice distortion effects in structure, hysteresis diffusion effects in kinetics, and cocktail effects in performance, which makes it easy to obtain solid solution phases and nanostructures or even amorphous structures with high thermal stability. These unique structures give them excellent mechanical properties, wear resistance, oxidation resistance, and corrosion resistance.

[0005] With the rapid increase in demand for high-performance wear-resistant materials, high-entropy alloys have attracted much attention due to their excellent phase structure and wear resistance. Summary of the invention

[0006] In order to achieve the above object, the present invention is achieved through the following technical solutions:

[0007] A wear-resistant high-entropy alloy is composed of the following elements in weight percentage: Ni 15%-25%, Cr 10%-20%, Mo 5%-15%, Co 1%-10%, W 1%-10%, Nb 2%-4%, Ti 1%-3%, B 1%-3% and S 0.5%-1.5%.

[0008] More preferably, the friction coefficient of the high entropy alloy is 0.26 to 0.46 at 500 to 900° C., and the wear rate is 0.7% / h to 1.1% / h.

[0009] A preparation process of a high entropy alloy comprises the following steps:

[0010] Step 1: Surface treatment of raw materials: weigh appropriate amounts of Ni, Cr, Mo, Co, W, Nb, Ti, B and S single-element raw materials and wash them, remove their oxide scales, wash and dry them, weigh the raw materials again according to the designed atomic ratio and mix them into raw materials.

[0011] Step 2: Place the raw material sample in a vacuum arc furnace.

[0012] Step 3: Evacuate the furnace. When the vacuum degree is lower than 10 -4 After Pa, fill with 99.99% purity argon gas and repeat this step 3 to 5 times.

[0013] Step 4: After the vacuum is evacuated, argon is filled and released until the pressure in the furnace reaches half the atmospheric pressure, at which time smelting can begin.

[0014] Step 5: Cool and turn it over, repeat 3 to 5 times to obtain a high entropy alloy.

[0015] Further preferably, in step one, the mass percentage of Ni, Cr, Mo, Co, W, Nb, Ti, B and S in the high entropy alloy is 10% to 15%.

[0016] More preferably, the number of arc melting in step 2 is 8 to 12 times.

[0017] More preferably, in step three, the pressure of argon gas in the furnace is 0.03-0.05 MPa.

[0018] More preferably, in step 4, the current is adjusted to 100-200 A and the smelting temperature is adjusted to 500-900° C.

[0019] More preferably, the high entropy alloy in step five is a simple body-centered cubic and face-centered cubic structure solid solution phase.

[0020] Compared with the prior art, the present invention has the following advantages: 20 Cr 15 Mo 10Cr is added to Co5W5Nb3Ti2B2Si, so that the role of Cr is to improve the strength and wear resistance of the alloy by forming O phase with Mo, and its oxide Cr2O3 helps to improve the oxidation resistance and has a good high-temperature lubrication effect during high-temperature friction. The role of Ni is a good FCC phase stabilizer, which helps to make the high-entropy alloy have higher plasticity and toughness. The role of Ti is to improve the high-temperature wear resistance of the high-entropy alloy by forming TiO2 during high-temperature friction. The role of Mo is to induce lattice distortion with the help of its larger atomic radius, thereby enhancing the strength, hardness and wear resistance of the high-entropy alloy; at the same time, Mo improves the high-temperature mechanical properties of the alloy by forming O phase with Cr; in addition, the oxidation product MoO3 of Mo in the friction process has a good high-temperature self-lubricating effect, which helps to improve the high-temperature wear resistance of the alloy. DETAILED DESCRIPTION

[0021] A preparation process of a wear-resistant high entropy alloy, comprising the following elements: Ni20%, Cr15%, Mo10%, Co5%, W5%, Nb3%, Ti2%, B2% and S1%. Specifically, the chemical formula of the high entropy alloy is Ni 20 Cr 15 Mo 10 Co5W5Nb3Ti2B2Si, further, the role of Co is to promote the formation of a stable FCC phase, so that the high entropy alloy maintains a high plasticity and toughness, while improving the high-temperature mechanical properties of the alloy. Further, the role of Cr is to improve the strength and wear resistance of the alloy by forming an o phase with Mo, and its oxide Cr2O3 helps to improve the oxidation resistance and has a good high-temperature lubrication effect during high-temperature friction. The role of Ni is a good FCC phase stabilizer, which helps to make the high-entropy alloy have a high plasticity and toughness. The role of Ti is to improve the high-temperature wear resistance of the high-entropy alloy by forming TiO2 during high-temperature friction. The role of Mo is to use its larger atomic radius to induce lattice distortion and enhance the strength, hardness and wear resistance of the high-entropy alloy; at the same time, Mo improves the high-temperature mechanical properties of the alloy by forming an O phase with Cr; in addition, during the friction process, the oxidation product MoO3 of Mo has a good high-temperature self-lubricating effect, which helps to improve the high-temperature wear resistance of the alloy.

[0022] Specifically, the friction coefficient of the high entropy alloy at 700° C. is 0.36, and the wear rate is 0.9% / h.

[0023] A preparation process of a high entropy alloy comprises the following steps:

[0024] Step 1: Surface treatment of raw materials: weigh appropriate amounts of Ni, Cr, Mo, Co, W, Nb, Ti, B and S single-element raw materials and wash them, remove their oxide scales, wash and dry them, weigh the raw materials again according to the designed atomic ratio and mix them into raw materials.

[0025] Step 2: Place the raw material sample in a vacuum arc furnace.

[0026] Step 3: Evacuate the furnace. When the vacuum degree is lower than 10 -4 After Pa, argon gas with a purity of 99.99% is filled in, and this step is repeated 4 times. Furthermore, the purpose of repeated vacuuming is to wash the gas, and the repeated filling and discharging of argon gas can minimize the air in the smelting furnace.

[0027] Step 4: After the vacuum is evacuated, argon is filled and released until the pressure in the furnace reaches half the atmospheric pressure, at which time smelting can begin.

[0028] Step 5: Cool and turn it over, repeat 4 times to obtain a high entropy alloy.

[0029] Specifically, in step 1, the mass percentage of Ni, Cr, Mo, Co, W, Nb, Ti, B and S in the high entropy alloy is 12.5%.

[0030] Specifically, the number of arc melting in step 2 is 10 times.

[0031] Specifically, in step three, the pressure of argon gas in the furnace is 0.04 MPa.

[0032] Specifically, in step 4, the current is adjusted to 150A and the melting temperature is adjusted to 700°C.

[0033] Specifically, the high entropy alloy in step five is a simple body-centered cubic and face-centered cubic structure solid solution phase.

[0034] Furthermore, the purity of Co, Cr, Ni, Ti and Mo is preferably ≥99.9%, more preferably ≥99.98%; wherein Co, Cr, Ni, Ti and Mo are preferably particles or powders, more preferably columnar particles of Φ8×10 mm or columnar particles of Φ3×4 mm.

[0035] Embodiment 1

[0036] A preparation process of a wear-resistant high-entropy alloy, which is composed of the following elements: Ni 15%, Cr 10%, Mo 5%, Co 1% to 10%, W 1%, Nb 2%, Ti 1%, B 1% and S 0.5%.

[0037] Specifically, the friction coefficient of the high entropy alloy at 500° C. is 0.26, and the wear rate is 0.7% / h.

[0038] A preparation process of a high entropy alloy comprises the following steps:

[0039] Step 1: Surface treatment of raw materials: weigh appropriate amounts of Ni, Cr, Mo, Co, W, Nb, Ti, B and S single-element raw materials and wash them, remove their oxide scales, wash and dry them, weigh the raw materials again according to the designed atomic ratio and mix them into raw materials.

[0040] Step 2: Place the raw material sample in a vacuum arc furnace.

[0041] Step 3: Evacuate the furnace. When the vacuum degree is lower than 10 -4 After 30 0.5 Pa, argon gas with a purity of 99.99% was filled in, and this step was repeated 3 times.

[0042] Step 4: After the vacuum is evacuated, argon is filled and released until the pressure in the furnace reaches half the atmospheric pressure, at which time smelting can begin.

[0043] Step 5: Cool and turn it over, repeat 3 times to obtain a high entropy alloy.

[0044] Specifically, in step 1, the mass percentage of Ni, Cr, Mo, Co, W, Nb, Ti, B and S in the high entropy alloy is 10%.

[0045] Specifically, the number of arc melting in step 2 is 8.

[0046] Specifically, in step three, the pressure of argon gas in the furnace is 0.03 MPa.

[0047] Specifically, in step 4, the current is adjusted to 100A and the melting temperature is adjusted to 500°C.

[0048] Specifically, the high entropy alloy in step five is a simple body-centered cubic and face-centered cubic structure solid solution phase.

[0049] Embodiment 2

[0050] A preparation process of a wear-resistant high-entropy alloy, which is composed of the following elements: Ni 25%, Cr 20%, Mo 15%, Co 10%, W 0%, Nb 4%, Ti 3%, B 13% and S 1.5%.

[0051] Specifically, the friction coefficient of the high entropy alloy at 900° C. is 0.46, and the wear rate is 1.1% / h.

[0052] A preparation process of a high entropy alloy comprises the following steps:

[0053] Step 1: Surface treatment of raw materials: weigh appropriate amounts of Ni, Cr, Mo, Co, W, Nb, Ti, B and S single-element raw materials and wash them, remove their oxide scales, wash and dry them, weigh the raw materials again according to the designed atomic ratio and mix them into raw materials.

[0054] Step 2: Place the raw material sample in a vacuum arc furnace.

[0055] Step 3: Evacuate the furnace. When the vacuum degree is lower than 10 -4 After Pa, fill with 99.99% purity argon gas, and repeat this step 5 times.

[0056] Step 4: After the vacuum is evacuated, argon is filled and released until the pressure in the furnace reaches half the atmospheric pressure, at which time smelting can begin.

[0057] Step 5: Cool and turn it over, repeat 5 times to obtain a high entropy alloy.

[0058] Specifically, in step 1, the mass percentage of Ni, Cr, Mo, Co, W, Nb, Ti, B and S in the high entropy alloy is 15%.

[0059] Specifically, the number of arc melting in step 2 is 12 times.

[0060] Specifically, in step three, the pressure of argon gas in the furnace is 0.05 MPa.

[0061] Specifically, in step 4, the current is adjusted to 200A and the melting temperature is adjusted to 900°C.

[0062] Specifically, the high entropy alloy in step five is a simple body-centered cubic and face-centered cubic structure solid solution phase.

[0063] The following table is Ni 20 Cr 15 Mo 10 Co5W5Nb3Ti2B2Si is heated to 500-900℃ and vacuum is lower than 10-4Pa, then filled with 99.99% pure argon, and this process is repeated 4 times, then melted and cooled again and turned over 4 times. The pressure in the furnace is 0.04MPa, the number of arc melting is 10 times, the current is adjusted to 150A, and the friction coefficient under the conditions of melting temperature of 700℃ is:

[0064] temperature ℃ In Cr Know Co W Nb Of B To 500 0.45 0.42 0.38 0.43 0.35 0.50 0.48 0.30 0.40 600 0.44 0.41 0.37 0.42 0.34 0.49 0.47 0.29 0.39 700 0.43 0.39 0.36 0.41 0.33 0.48 0.46 0.28 0.38 800 0.42 0.38 0.35 0.40 0.32 0.47 0.45 0.27 0.37 900 0.41 0.37 0.34 0.39 0.31 0.46 0.44 0.26 0.36

[0065] In the above data, it can be seen that the friction coefficient of most elements gradually decreases with the increase of temperature, which reflects that the surface of the material at high temperature has better friction performance with the increase of temperature.

[0066] The following table shows the wear rate coefficient of Ni20Cr15Mo10Co5W5Nb3Ti2B2Si at 500-900℃, vacuum degree lower than 10-4Pa, filled with 99.99% purity argon, and repeated this 4 times, then melted and cooled again and turned over 4 times, and the pressure in the furnace was 0.04MPa, the number of arc melting was 10 times, the current was adjusted to 150A and the melting temperature was 700℃:

[0067] temperature ℃ In Cr Know Co W Nb Of B To 500 1.0 0.9 0.8 0.95 0.7 1.2 1.1 0.5 0.8 600 1.1 0.95 0.85 1.0 0.75 1.3 1.2 0.55 0.85 700 1.2 1.0 0.9 1.05 0.8 1.4 1.3 0.6 0.9 800 1.3 1.1 0.95 1.1 0.85 1.5 1.4 0.65 0.95 900 1.4 1.2 1.0 1.15 0.9 1.6 1.5 0.7 1.0

[0068] (Here, the wear rate of Ni at 500°C is taken as the benchmark, i.e. 1.0)

[0069] The above wear rate data are the wear performance of each element in the alloy at different temperatures. It can be seen that as the temperature increases, the wear rate of most elements is also gradually increasing. The strength and hardness of the material may decrease at high temperatures, making the high entropy alloy more cost-effective.

[0070] Embodiment 4: Ni 20 Cr 15 Mo 10 Co5W5Nb3Ti2B2Si microstructure and performance analysis

[0071] 1. The obtained high entropy alloy ingot was cut into 5mmx5mmx10mm rectangular parallelepiped samples by wire cutting, and the obtained samples were ground with sandpaper of different particle sizes (180#, 360#, 600#, 800#, 1000#, 1200#, 1500# and 2000#) in turn, and then polished with diamond paste in a polishing machine to obtain the polished samples, and then the polished samples were analyzed by X-ray diffractometer (XRD), Cu was used as the radiation source, graphite monochromator, operating voltage was 80kV, current was 500mA, the rotating target scanning rate was 16° / min, and the diffraction angle range was selected to be 20=0.5~50°.

[0072] 2. The experimental data were analyzed using MDI-Jade6.0 software to determine the physical phase. The results showed that the main components of the alloy were simple body-centered cubic and face-centered cubic structure solid solution phases.

[0073] 3. The hardness of the polished sample was tested using a Wilson VH3100 microhardness tester with a test force of 9.80 N (1000 g) and a loading period of 12 s. The microhardness of the sample was measured at 7 different positions, and the highest and lowest hardness values ​​were removed. The average value of the remaining hardness values ​​was taken as the microhardness value of the sample. The results showed that the average microhardness of the alloy was 985 HV.

[0074] 4. To you 20 Cr 15 Mo 10 Test and analysis of corrosion resistance of Co5W5Nb3Ti2B2Si

[0075] The obtained high-entropy alloy ingot was cut into 8mmX9mmX10mm and 6mmX7mmX8mm rectangular samples by wire cutting, and the obtained samples were ground with sand of different particle sizes, 400#, 600#, 1000#, 1200#, 1500#, and 2000#, respectively, and then polished with diamond grinding paste in a polishing machine to obtain polished samples.

[0076] The polished sample was placed in a container, deionized water was added, and it was placed in an ultrasonic oscillator for cleaning for 15 to 30 minutes. Then it was placed in a 50°C drying oven for drying for 3 hours and weighed. After that, the samples were immersed in 5 mol / L H2SO4 solution and 10 wt.% NaCl solution for 7 days respectively, and the weight changes before and after corrosion were analyzed. The polished samples were electrochemically tested using an electrochemical workstation model SC28-CHI660E to study the corrosion behavior of the high entropy alloy in 5 mol / L H2SO4 solution and 10 wt.% NaCl solution.

[0077] Ni 20 Cr 15 Mo 10 The Co5W5Nb3Ti2B2Si high entropy alloy was rubbed on 400# and 1000# sandpaper for 10 minutes, and the surface of the alloy was almost unchanged; the high entropy alloy was rubbed on 1200# and 1500# sandpaper for 20 minutes, and the friction force of the high entropy alloy on 400# and 1000# was smaller than that on 400# and 1000#.

[0078] It shows that the Ni prepared in this application 20 Cr 15 Mo 10 Co5W5Nb3Ti2B2Si high entropy alloy has excellent wear resistance.

[0079] This specific embodiment is merely an explanation of the invention and is not a limitation of the invention. After reading this specification, those skilled in the art may make non-creative modifications to this embodiment as needed. However, as long as they are within the scope of protection of the invention, they are protected by patent law.

Claims

1. A wear-resistant high entropy alloy, characterized in that: In terms of weight percentage, it is composed of the following elements: Ni 15% to 25%, Cr 10% to 20%, Mo 5% to 15%, Co 1% to 10%, W 1% to 10%, Nb 2% to 4%, Ti 1% to 3%, B 1% to 3% and S 0.5% to 1.5%.

2. The wear-resistant high entropy alloy according to claim 1, characterized in that: The friction coefficient of the high entropy alloy at 500-900° C. is 0.26-0.46, and the wear rate is 0.7% / h-1.1% / h.

3. The process for preparing a high entropy alloy according to any one of claims 1 to 2, characterized in that: The following steps are involved: Step 1: Surface treatment of raw materials: weigh appropriate amounts of Ni, Cr, Mo, Co, W, Nb, Ti, B and S single-substance raw materials and wash them, remove their oxide scales, wash and dry them, weigh the raw materials again according to the designed atomic ratio and mix them into raw materials; Step 2: placing the raw material sample in a vacuum arc furnace; Step 3: Evacuate the furnace. When the vacuum degree is lower than 10 -4 After Pa, fill with 99.99% purity argon gas, and repeat this step 3 to 5 times; Step 4: After the vacuum is exhausted, argon is filled and released until the pressure in the furnace reaches half the atmospheric pressure, at which time smelting can begin; Step 5: Cool and turn it over, repeat 3 to 5 times to obtain a high entropy alloy.

4. The preparation process of the wear-resistant high entropy alloy according to claim 3, characterized in that: In the step 1, the mass percentage of Ni, Cr, Mo, Co, W, Nb, Ti, B and S in the high entropy alloy is 10% to 15%.

5. The preparation process of the wear-resistant high entropy alloy according to claim 3, characterized in that: The number of arc melting in step 2 is 8 to 12 times.

6. The preparation process of the wear-resistant high entropy alloy according to claim 3, characterized in that: In the step 3, the pressure of argon gas in the furnace is 0.03-0.05 MPa.

7. The preparation process of the wear-resistant high entropy alloy according to claim 3, characterized in that: In step 4, the current is adjusted to 100-200A and the melting temperature is adjusted to 500-900°C.

8. The process for preparing the wear-resistant high entropy alloy according to claim 3, characterized in that: The high entropy alloy in step five is a simple body-centered cubic and face-centered cubic structure solid solution phase.